The genus Beccarinda Kuntze (Gesneriaceae) in the flora of Vietnam - Phuong, Vu Xuan (Academia Journal of Biology, 2014)
The genus Beccarinda Kuntze (Gesneriaceae) has 8 species, distributing in South Asia. There was one species Slackia tonkinensis Pellegr. (1926) in Vietnam but [7] it was renamed as Beccarinda tonkinensis (Pellegr.) Burtt. by Burtt in 1955 [2]. During the study of specimens and documents of Gesneriaceae of Vietnam, we have found one new species Beccarinda erythrotricha W. T. Wang for the flora of Vietnam. It has some especial characters as herbs, perennial. Stems 10-20 cm, leaves often crowded near stem apex, blade elliptic to ovate, base broadly cuneate to nearly rounded, sparsely villous or hirsute, abaxially densely purple-red pubescent along midrib and lateral veins. The specimens were collected in the Laocai (Vanban district) and Hagiang (Yenminh district) provinces and deposited in the Hanoi herbarium, Institute of Ecology and Biological resources, Hanoi, Vietnam (HN). Thus, there are 2 species of this genus in Vietnam.